A Rapid Evidence Assessment of the effectiveness of prison education in reducing recidivism and increasing employment. (June 2017) - Ellison, Mark; Szifris, Kirstine; Horan, Rachel; Fox, Chris
This is a Rapid Evidence Assessment (REA) of educational programmes delivered within prison. Included in this review are evaluations of vocational, academic, basic skills, accredited and unaccredited educational provision in prison where recidivism and/or employment were measured as outcomes. Initial searches returned 4304 titles and abstracts. Of these, 28 papers met the criteria for inclusion. Only 18 papers provided sufficient information and robust enough research design to be included in the meta-analysis. Meta-analysis on 18 reoffending studies identified that delivering education in prison settings has a positive impact on recidivism. Overall, the pooled odds ratio indicates a reduction in the likelihood of recidivating of approximately one-third (0.64 = 64%∼2/3). Meta-analysis on five employment studies identified that education in prison settings has a positive impact on employment. Overall, odds ratios indicated a 24 per cent increase in likelihood of gaining employment if the prisoner engages in prison education. However, this is based on a small number of papers with statistical findings being less robust and evidence drawn largely from the USA.